Legal Implications of Financial Services Authority Regulation Number 30 of 2024 on the Financial Conglomerate System in Indonesia - Prasada, Erisa Ardika; Putri, Rizha Claudilla; Nurfitrah, Mesya Assauma (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: Financial conglomeration in Indonesia is a strategy of combining companies from different sectors to diversify income and reduce risk.Purposes of the Research: This research aims to analyze the Financial Services Authority Regulation Number: 30/2024, which aims to harmonize the provisions of financial conglomeration with Law Number: 4/2023 on Financial Sector Development and Strengthening.Methods of the Research: The method used is normative research, focusing on analyzing legal norms and related policies.Findings of the Research: The results show that Financial Services Authority Regulations Number 30/2024 introduces a Financial Conglomerate Holding Company that is responsible for the control and consolidation of conglomerate members. The implementation of integrated supervision is expected to enhance financial system stability and support inclusive and sustainable economic growth. This research provides insight into the challenges and opportunities in regulating financial conglomerates in Indonesia.